Visual exploratory activity in elite women`s soccer: an analysis of the UEFA Women`s European Championship 2022 - Feist, J.; Datson, N.; Runswick, O. R.; Harkness-Armstrong, A.; Pocock, C. (International Journal of Sport and Exercise Psychology, 2025)
Recent research has developed understanding of the technical and tactical determinants of success in elite women`s soccer, however a lack of research exists on analysing how elite female players visually explore their environment to support skilled soccer performance. This study aimed to describe the visual exploratory activity (VEA) of elite female central midfield players and understand the relationships between VEA, performance with the ball and specific contextual and situational factors. Thirty female central midfield players (M age = 26.7 years, SD = 3.8) from the eight teams who competed in the knock-out stages of UEFA Women`s European Championship 2022 were analysed. Television broadcast and UEFA tactical footage were combined to analyse players across the seven knock-out stage matches, totalling 1,038 individual ball possessions. The mean scan frequency before receiving the ball was 0.35 scans/second. Results showed pitch location when receiving the ball to be the main predictor of scan frequency, which in turn predicted action result (p = 0.003) and turn with the ball (p = 0.003). Scan frequencies were lower compared to men`s elite and academy players. This study sets a platform for experimental research to further our understanding of VEA and performance with the ball in women`s soccer.